La lúdica como estrategia pedagógica en la resolución de conflictos en el aula (2021)
The present research project arises from an educational problem contemplating within the coexistence and the school climate inside and outside the classroom, this is how this research is developed with the purpose of proposing ludic-pedagogical strategies, oriented towards the resolution conflict in the classroom. Thus, it will help teachers to strengthen and improve coexistence in 5th grade students of the Francisco Cartusciello Commercial Technical Educational Institution, headquarters No. 4 Santa Rita de Cascia in the municipality of Sabanagrande-Atlántico. In such a way that for this research a socio-critical paradigm has been used that describes the event in which it takes place, starting from a rigorous contextual description, of a fact or situation that guarantees maximum subjectivity in the training of a complex reality, with an introspective epistemological approach in this there is an understanding between the subject and the context all this through a dialogical method in which the researcher participates under a qualitative approach, because it makes the distinction between the meanings imposed by the researcher and those generated by those investigated, having special importance the perceptions and motivations of the subjects of analysis themselves, which become the bases of the analytical conclusions.